Metabolic Pathway of Cardiospecific Troponins: From Fundamental Aspects to Diagnostic Role (Comprehensive Review) - Chaulin, Aleksey M. (Frontiers in Molecular Biosciences, 2022)
Many molecules of the human body perform key regulatory functions and are widely used as targets for the development of therapeutic drugs or as specific diagnostic markers. These molecules undergo a significant metabolic pathway, during which they are influenced by a number of factors (biological characteristics, hormones, enzymes, etc.) that can affect molecular metabolism and, as a consequence, the serum concentration or activity of these molecules. Among the most important molecules in the field of cardiology are the molecules of cardiospecific troponins (Tns), which regulate the processes of myocardial contraction/relaxation and are used as markers for the early diagnosis of ischemic necrosis of cardiomyocytes (CMC) in myocardial infarction (MI). The diagnostic value and diagnostic capabilities of cardiospecific Tns have changed significantly after the advent of new (highly sensitive (HS)) detection methods. Thus, early diagnostic algorithms of MI were approved for clinical practice, thanks to which the possibility of rapid diagnosis and determination of optimal tactics for managing patients with MI was opened. Relatively recently, promising directions have also been opened for the use of cardiospecific Tns as prognostic markers both at the early stages of the development of cardiovascular diseases (CVD) (arterial hypertension (AH), heart failure (HF), coronary heart disease (CHD), etc.), and in non-ischemic extra-cardiac pathologies that can negatively affect CMC (for example, sepsis, chronic kidney disease (CKD), chronic obstructive pulmonary disease (COPD), etc.). Recent studies have also shown that cardiospecific Tns are present not only in blood serum, but also in other biological fluids (urine, oral fluid, pericardial fluid, amniotic fluid). Thus, cardiospecific Tns have additional diagnostic capabilities. However, the fundamental aspects of the metabolic pathway of cardiospecific Tns are definitively unknown, in particular, specific mechanisms of release of Tns from CMC in non-ischemic extra-cardiac pathologies, mechanisms of circulation and elimination of Tns from the human body, mechanisms of transport of Tns to other biological fluids and factors that may affect these processes have not been established. In this comprehensive manuscript, all stages of the metabolic pathway are consistently and in detail considered, starting from release from CMC and ending with excretion (removal) from the human body.